Evolution of maritime logistics in the age of supply chain management - Foo, Heng Aik. (2009)
The growth of the Third Party Logistics (3PL) business has caused many firms from different industries to enter the field. Ocean carriers are one of the rivals of traditional 3PLs. They are transforming their roles in shippers’ supply chain from mere sea transportation provider to total logistics providers. We are interested to know the driving forces behind the changes and how the changes affect the ocean carriers. In the process of transformation, they have encountered some challenges that impede the freight integration. They have to utilise their strengths and overcome their weaknesses in order to succeed. Three case studies have been done to evaluate the current strategies of ocean carriers. A number of best practices had been identified in the case studies. However, there is no single strategy that can suit all ocean carriers. The best strategy is the mixture of a number of best practices. Of course, it must be set based on the vision, resource, and strengths of particular ocean carrier.